Developing procurement practices framework in supply chain of oil and gas sector: a case study of Gastec Company in Egypt - Mustafa, Mirna Muhammad; al-Saqati, Khalid Jabir Abd Allah (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2023)
The main aim of this research is to find out the impact of developing procurement practices on supply chain management. developing the procurement practices in general will contribute in solving one of the major problems affecting the supply chain procedures nowadays in Egypt, and specifically will allow oil & gas companies to manage supply chain risks and achieve operational efficiency. this research used the analytical method and descriptive method through inductive approach. this research was based on an investigation that aspires to test theory through developing of objectives regarding to impact of procurement on supply chain performance. the study tested the mentioned variables hence modifying the theory in light of the findings. therefore, the adoption of inductive approach was appropriate for this study. the study used questionnaire as a data collection tool to collect a primary data. the study found that Gastec was experiencing a number of issues, the most significant of which is that the internal departments are not connected to each other by a unified electronic system, and the business also does not rely on an electronic system to manage its procurement procedures, which is the thesis' main focus. الهدف الرئيسي من هذا البحث هو معرفة تأثير تطوير ممارسات الشراء على إدارة سلسلة التوريد. سيساهم تطوير ممارسات الشراء بشكل عام في حل إحدى المشكلات الرئيسية التي تؤثر على إجراءات سلسلة التوريد في الوقت الحاضر في مصر، وسيسمح على وجه التحديد لشركات النفط والغاز بإدارة مخاطر سلسلة التوريد وتحقيق الكفاءة التشغيلية استخدم هذا البحث المنهج التحليلي والمنهج الوصفي من خلال المنهج الاستقرائي استند هذا البحث إلى تحقيق يطمح إلى اختبار النظرية من خلال تطوير الأهداف المتعلقة بتأثير الشراء على أداء سلسلة التوريد اختبرت الدراسة المتغيرات المذكورة ومن ثم تعديل النظرية في ضوء النتائج لذلك، كان اعتماد النهج الاستقرائي مناسبا لهذه الدراسة. استخدمت الدراسة الاستبيان كأداة لجمع البيانات الأولية. ووجدت الدراسة أن شركة غازتك كانت تواجه عددا من القضايا، من أهمها أن الإدارات الداخلية غير مرتبطة ببعضها البعض بنظام إلكتروني موحد، كما أن العمل لا يعتمد على نظام إلكتروني لإدارة إجراءات الشراء الخاصة به، وهو المحور الرئيسي للبحث.